Impact of a physical activity program on the anxiety, depression, occupational stress and burnout syndrome of nursing professionals - Anderson Rodrigues Freitas; Estela Cristina Carneseca; Carlos Eduardo Paiva; Bianca Sakamoto Ribeiro Paiva (Universidade de São Paulo, 2014)
OBJECTIVE: to assess the effects of a workplace physical activity (WPA) program on levels of anxiety, depression, burnout, occupational stress and self-perception of health and work-related quality of life of a nursing team in a palliative care unit.METHODS: the WPA was conducted five days per week, lasting ten minutes, during three consecutive months. Twenty-one nursing professionals were evaluated before and after the intervention, with the Hospital Anxiety and Depression Scale, the Maslch Burnout Inventory, and the Job Stress Scale. The changes in self-perceived health and work-related quality of life were measured using a semi-structured questionnaire.RESULTS: the WPA did not yield significant results on the levels of anxiety, depression, burnout or occupational stress. However, after the intervention, participants reported improved perceptions of bodily pain and feeling of fatigue at work.CONCLUSION: the WPA did not lead to beneficial effects on occupational stress and psychological variables, but it was well accepted by the nursing professionals, who reported improvement in perceptions of health and work-related quality of life.